2018
DOI: 10.1016/j.hrthm.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Defibrillation testing is mandatory in patients with subcutaneous implantable cardioverter–defibrillator to confirm appropriate ventricular fibrillation detection

Abstract: Our study demonstrated a marked sensing delay leading to prolonged time to therapy in a large number of S-ICD patients. A few worrisome cases of noise oversensing inhibiting the therapies were detected. These results support the need for systematic intraoperative defibrillation testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Data on the position of the S-ICD system were inconclusive. 3 In consonance with this previous article, in this case we describe a similar sensing issue leading to inhibition of shock therapy during DFT following elective S-ICD replacement. Within our tertiary center with 10 years of S-ICD experience, 375 de novo S-ICD implants and 140 S-ICD box changes, this was the first and only observed case of noise during DFT with subsequent inhibition of shock therapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Data on the position of the S-ICD system were inconclusive. 3 In consonance with this previous article, in this case we describe a similar sensing issue leading to inhibition of shock therapy during DFT following elective S-ICD replacement. Within our tertiary center with 10 years of S-ICD experience, 375 de novo S-ICD implants and 140 S-ICD box changes, this was the first and only observed case of noise during DFT with subsequent inhibition of shock therapy.…”
Section: Discussionsupporting
confidence: 81%
“…2 A recently published multicenter study described inhibition of shock therapy during defibrillation testing (DFT) in 5 de novo S-ICD implantations owing to noise sensing. 3 Hypothetically, muscle spasm intrinsic to the 200 mA burst by the S-ICD during induction of ventricular fibrillation (VF) may have caused noise with subsequent absence of VF detection and withholding of therapy. However, to our knowledge there is no evidence that supports this concept to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, all patients with S‐ICD should not indicate improved DFT with lead repositioning, as a previous computer modeling study reported that a right parasternal S‐ICD lead increased DFT . Meanwhile, another previous study reported a patient with S‐ICD showing improved DFT with lead repositioning to the right parasternal position, as shown in this case . The positional relationship among the lead, generator, and heart was changed by lead repositioning from the left to the right sternal border, which may have contributed to improved shock vector for the heart.…”
Section: Discussionmentioning
confidence: 65%
“…9,10 However, right-sided and subcutaneous ICDs were not included in these studies, with subsequent studies noting the importance of defibrillation testing in sub-cutaneous ICDs. 11 Studies on right-sided implants are lacking. Interactive simulations of defibrillation models 12 have noted that right-sided ICDs have higher defibrillation thresholds.…”
Section: Discussionmentioning
confidence: 99%